THE EFFECT OF ACUPRESSURE TO DECREASE PAIN LEVELS IN POSTPARTUM WOMEN - Dwining Handayani; Bagus Dwi Cahyono (UNEJ e-Proceeding, 2020)
Background: Postpartum pain experienced by every mother was a subjective and physiological experience. This is due to increased hormones oxytocin and prolactin, causing uterine contractions after the placenta and the baby was born. The acupressure technique was a non-pharmacological technique aimed at reducing the level of pain in postpartum mothers. This technique has never been applied in dr. R. Soedarsono Pasuruan general hospital. Purpose: This study aimed was to determine the effect of acupressure to decrease pain levels in postpartum women. Method: The population in this study were postpartum women, with a sample of 16 people. The study used One group, pre-post test design with systematic random sampling. VAS (Visual Analog Scale) was used to collect the data. The data analyzed with Wilcoxon test (α =0,05). Result: The results showed that before acupressure 62,5% postpartum women experienced moderate pain (10 people). After acupressure 62.5% postpartum women experienced mild pain (10 people). The statistic test result showed p= 0,00 (p < α) so Ha was accepted. Conclusion: It can be concluded that acupressure has an effect on reducing the pain level of postpartum women because the emphasis on acupressure points stimulates local endorphin production, thereby activating the pain inhibition mechanism. It was recommended that health workers use acupressure non-pharmacological techniques for postpartum women so that pain can be minimized without adverse effects. Keywords: Acupressure; Pain; Postpartum